Comparative study of systemic and local delivery of mesenchymal stromal cells for the treatment of chronic kidney disease - Gregersen, Emil; Kresse, Jean-Claude; Atay, Jasmine Cicek Leifing; Boysen, Anders Toftegaard; Nejsum, Peter; Eijken, Marco; Nørregaard, Rikke (Frontiers in Cell and Developmental Biology, 2024)
Renal fibrosis, characterized by excessive extracellular matrix accumulation, leads to a progressive decline of renal function and is a common endpoint of chronic kidney disease (CKD). Current treatments primarily focus on managing underlying diseases, offering limited direct intervention for the fibrotic process. This study explores the anti-fibrotic potential of human adipose-derived mesenchymal stromal cells (MSCs) and their derived extracellular vesicles (EVs) in the context of CKD, emphasizing the effects of systemic versus local delivery methods. Preconditioned MSCs (Pr-MSCs) were treated with TNF-α and IFN-γ to enhance their immunomodulatory capabilities, and demonstrated significant anti-fibrotic effects in vitro, reducing mRNA expression of fibrosis markers in TGF-β stimulated HKC-8 cells.Our in vivo findings from a murine unilateral ureteral obstruction (UUO) model of CKD showed that local deliveries of Pr-MSCs reduced collagen deposition and increased expression of the anti-inflammatory cytokine IL-10. Systemic administration of Pr-MSCs did not show any significant effect on UUO-induced injury. In addition, EVs did not replicate the anti-fibrotic effects observed with their parent cells, suggesting that soluble proteins or metabolites secreted by Pr-MSCs might be the primary mediators of the anti-fibrotic and immunomodulatory effects. This study provides critical insights into the therapeutic efficacy of MSCs, highlighting the importance of delivery methods and the potential of preconditioning strategies in enhancing MSC-based therapies for renal fibrosis.